The pregnancy as a inducting factor of intrinsic pathway of apoptosis in kidney’s cells of female rats - Pedrycz, Agnieszka; Siermontowski, Piotr; Orłowski, Marcin (Current Problems of Psychiatry, 2011)
The aim of this study was immunohistochemical evaluation of intrinsic pathway of apoptosis in renal epithelial cells in pregnant rats including time. We evaluated in immunohistochemical way expression of the initiating caspase 9 – activated during apoptosis in protein complex-apoptosome. Rats used in this experiment was divided into 4 groups – 8 individuals each: I group – female rats which was fertilized and decapitated in 10 day of pregnancy, II group female rats which was fertilized and decapitated in 20 day of pregnancy III group female rats which was fertilized and decapitated in 10 day after delivery VI group – control – female rats which decapitated in 30 day of experiment. Specimens of kidneys taken to examine we analyzed in immunohistochemical standard three-step method detecting caspse 9 protein. Immunohistochemical positive reaction increased in all experimental groups compared to control. Pregnancy – induced hormonal changes in rats body activated apoptosis of renal cells via intrinsic pathway with active caspase 9. This pathway was the most intensive 10th day of pregnancy.